Propuesta Didáctica Para El Fortalecimiento De La Expresión Oral En Estudiantes De Quinto Grado De Primaria En Una Institución Privada De Bogotá A Través Del Video Educativo (2016)
The present work focuses on strengthening fifth graders’ oral expression at a private school in Bogotá through the use of video, as a pedagogical tool that allows students to Familiarize with social, family and school issues. The didactic unit “Learn to live together in peace” is supported by Learning Basic Rights and Citizenship Competences Basic Standars as the main shaft of students´ integral formation.